Effect of zinc supplementation during cryopreservation on post-thaw chicken semen parameters and fertility - Murugesan, Shanmugam; Mahapatra, Ramkrishna (Journal of the Hellenic Veterinary Medical Society, 2022)
The present study evaluated supplementation of zinc from different sources during chicken semen cryopreservation on post-thaw semen quality and fertility. Adult White Leghorn chicken semen was cryopreserved using 4% dimethyl sulfoxide (DMSO) in Sasaki diluent (SD). In the semen cryomixture zinc oxide (6.25 and 12.5 µM) and zinc sulphate (100 and 200 µM) was added and cryopreserved. The plastic semen straws were thawed at 5°C for 100 sec and samples were evaluated for sperm motility, live, abnormal and acrosome intact sperm. The lipid peroxidation in the seminal plasma was evaluated. The semen cryopreservation and evaluation were repeated on six occasions. Fertility of the zinc supplemented semen was evaluated by inseminating into White Leghorn hens. Zinc supplementation did not affect any of the post-thaw sperm parameters. The lipid peroxidation and fertility were similar between the treatments. In conclusion, supplementation of zinc as zinc oxide or zinc sulphate during chicken semen cryopreservation does not affect post-thaw semen parameters or fertility.